Gentlemen looking on at items displayed in an exhibition - Richardson, Dennis
This is a black and white photograph of gentlemen looking at items displayed in an exhibition.
Copyright- API. Daily News collection, no restriction.
Keywords: Exhibitions, Ja; Photograph